Using Bluetooth Low Energy for positioning systems within overcrowded environments: A real in-field evaluation. (July 2021) - Morgan, Ahmed A.; Humaid, Ghada S. Bin; Moustafa, Abdellatif I.
Abstract: Bluetooth Low Energy (BLE) is a widely-used technology for short-range proximity and distance estimation. The existence of human bodies is proved to influence BLE signals. In this paper, the effect of overcrowdedness on the performance of BLE-based positioning systems is studied. Real experiments are conducted in places with large and small areas. Both proximity and location beacons are evaluated with different transmission powers. Compared to uncrowded environments, results show random, but often manageable, changes in the received signal strength and position estimation accuracy. The logarithmic path loss model is found unsuitable for small areas and its parameters are noticeably affected by the crowdedness. Location beacons are found more robust against the increase in crowdedness than proximity counterparts. For these location beacons, the overcrowdedness maximally changes the signal strength by 8.6 dBm, the coverage range by 24 m, the proximity estimation accuracy by 18%, and the distance estimation accuracy by 41%. Graphical abstract: Highlights: The crowdedness causes random, but manageable, changes in BLE performance. The crowdedness noticeably affects parameters of the logarithmic path loss model. Location beacons have better estimation accuracy than proximity counterparts. Higher transmission power improves the accuracy but reduces the coverage range.